Antiphospholipid antibodies in black south africans with hiv and acute coronary syndromes: prevalence and clinical correlates - Becker, Anthony C (BioMed Central, 2011)
BACKGROUND: HIV infection is associated with a high prevalence of antiphospholipid antibodies (aPL) and increased thrombotic events but the aetiopathogenic link between the two is unclear. FINDINGS: Prospective single centre study from Soweto, South Africa, comparing the prevalence of aPL in highly active anti-retroviral therapy (HAART) naïve HIV positive and negative patients presenting with Acute Coronary Syndromes (ACS). Between March 2004 and February 2008, 30 consecutive black South African HIV patients with ACS were compared to 30 black HIV negative patients with ACS. The HIV patients were younger (43 ± 7 vs. 54 ± 13, p = 0.004) and besides smoking (73% vs. 33%, p = 0.002) and lower HDL levels (0.8 ± 0.3 vs. 1.1 ± 0.4, p = 0.001) had fewer risk factors than the control group. HIV patients had a higher prevalence of anticardiolipin (aCL) IgG (47% vs. 10%, p = 0.003) and anti-prothrombin (aPT) IgG antibodies (87% vs. 21%, p < 0.001) but there was no difference in the prevalence of the antiphospholipid syndrome (44% vs. 24%, p = N/S) and aPL were not predictive of clinical or angiographic outcomes. CONCLUSIONS: Treatment naïve black South African HIV patients with ACS are younger with fewer traditional coronary risk factors than HIV negative patients but have a higher prevalence and different expression of aPL which is likely to be an epiphenomenon of the HIV infection rather than causally linked to thrombosis and the pathogenesis of ACS.